The role of the peruvian state in the management of social conflicts - Díaz Bravo, José (2020)
The present article addresses essentially the role that the Peruvian State has been developing during the recent years in the management of social conflicts, starting from the statement that it always plays a main role in its three levels of government. This paper aims to corroborate the thesis that the manager role necessarily implies being a spokesperson, and that role has not being fully fulfilled by the Peruvian State, causing the management of social conflicts to be deficient.